(untitled) (Journal of Engineering, 2012)
Corrosion inhibiting admixtures are unique among other methods to protect reinforced concrete from corrosion damage. In this study, the effect of furfural on the fresh and hardened properties of concrete mixes of 35 and 45 MPa compressive strengths as well as the corrosion inhibition of furfural was evaluated. Furfural was added at different dosages (1, 2 and 3% by weight of cement) with and without superplasticizer (HRWR). Different electrochemical measurements were performed (Half-cell potential, Tafel plot and linear polarization resistance). Electrochemical measurements confirmed that furfural dramatically reduces the rate of corrosion; the inhibition efficiencies were 62.7 and 63.8 % due to 3% furfural addition to 35 and 45MPa-concretes respectively. Results also showed that the combined presence of furfural and HRWR was found to provide an excellent corrosion protection to steel.